Involvement of NRF2 and AMPK signaling in aging and progeria: a digest - Eleni Petsouki; Vasileios Gerakopoulos; Despoina D. Gianniou; Elke H. Heiss; Ioannis P. Trougakos (Redox Biology)
Aging refers to a gradual, continuous process of natural change which is accompanied by progressive loss in physiological functions and an increased risk of frailty, disease, and death. Cells face a declining capacity to adapt homeostasis after perturbation, resulting among others in an imbalance in reactive species production and damage removal, as well as in energy or nutrient sensing and usage. NRF2 (Nuclear factor E2 p45‐related factor 2) is a transcription factor primarily known to regulate the expression of genes involved in cellular defense against oxidative, proteotoxic, or xenobiotic stress. AMPK (AMP-activated protein kinase), a serine/threonine kinase, serves as a central sensor of cellular energy status, maintaining ATP levels by tweaking the ratio of anabolic and catabolic pathways. Cooperativity between AMPK and NRF2 signaling, which goes beyond mere parallel activation in situations of cellular stress, has been previously described. This narrative short review zooms in the current understanding of NRF2 and AMPK signaling, alone or in concert, in aging and Hutchinson–Gilford Progeria Syndrome (HGPS), a genetic disorder characterized by premature aging.